2014
DOI: 10.1145/2629497
|View full text |Cite
|
Sign up to set email alerts
|

Placement optimization of flexible TFT circuits with mechanical strain and temperature consideration

Abstract: Mobility is the primary device parameter affecting circuit performance in flexible thin-film transistor (TFT) technologies, and is particularly sensitive to the change of mechanical strain and temperature. However, existing algorithms only consider the impact of mechanical strain in cell placement of flexible TFT circuits. Without taking temperature into consideration, mobility may be dramatically decreased which leads to circuit performance degradation. This article presents the first work to minimize the mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study in [141] relied on a statistical timing analyzer (STA) to identify bending hotspots, and used the derived information together with TFT bending models [142] to generate a hotspot mapping for guiding circuit layout, followed by the cell placer's simulated annealing process for finding the optimized cell placement to minimize timing degradation under bending. The study in [143] further suggested inclusion of both mechanical strain and temperature drift's impacts on TFT circuit's performance in layout optimization. For bending or other use cases that require mechanical deformation or thermal cycles, FPE/FHE multi-physics models for electrical, mechanical, and thermal interactions must be comprehensive and accurate in order to derive useful information from multi-physics simulation.…”
Section: Design Automation For Flexible Printed Electronics (Fpes)mentioning
confidence: 99%
“…The study in [141] relied on a statistical timing analyzer (STA) to identify bending hotspots, and used the derived information together with TFT bending models [142] to generate a hotspot mapping for guiding circuit layout, followed by the cell placer's simulated annealing process for finding the optimized cell placement to minimize timing degradation under bending. The study in [143] further suggested inclusion of both mechanical strain and temperature drift's impacts on TFT circuit's performance in layout optimization. For bending or other use cases that require mechanical deformation or thermal cycles, FPE/FHE multi-physics models for electrical, mechanical, and thermal interactions must be comprehensive and accurate in order to derive useful information from multi-physics simulation.…”
Section: Design Automation For Flexible Printed Electronics (Fpes)mentioning
confidence: 99%